Issues of a new epoch: the coal strike Panama Philippines and Cuba (1904)
The coal strike. Panama republic and canal. Curse of the American government. Why the President was prompt. Complicity and treaty obligations. Colombia’s usurping government. Our work as civilizer. The new republic of Cuba. Peace and progress in the Philippines. The Friars lands.